1989
DOI: 10.1016/0885-3924(89)90023-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between asthenia and nutritional status, lean body mass, anemia, psychological status, and tumor mass in patients with advanced breast cancer

Abstract: Sixty-four consecutive patients with advanced breast cancer were included in a study designed to determine the prevalence of asthenia and its association with other clinical features. The Asthenia Score (AS, the average of four tests designed by our group to assess asthenia) was 59 +/- 9 for patients versus 88 +/- 7 for a group of 68 normal controls (p less than 0.001). Twenty-six patients (41%) scored below the tenth percentile of normal controls and were considered asthenics. AS was correlated with depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
13

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 15 publications
2
33
0
13
Order By: Relevance
“…Step 1 other studies which have found a positive relationship between these two constructs in patients with cancer (Bruera et al, 1989;Morant et al, 1993;Smets et al, 1996). The discrepancy may partly be explained by the nature of our patient sample.…”
Section: Patients Controlsmentioning
confidence: 52%
See 2 more Smart Citations
“…Step 1 other studies which have found a positive relationship between these two constructs in patients with cancer (Bruera et al, 1989;Morant et al, 1993;Smets et al, 1996). The discrepancy may partly be explained by the nature of our patient sample.…”
Section: Patients Controlsmentioning
confidence: 52%
“…Bruera and coworkers (Bruera et al, 1989) failed to find any such association in patients with advanced breast cancer, but concluded that this was probably due to their studying a relatively well nourished group of patients. In our study, despite a high prevalence of cachexia we were still unable to find an association between fatigue and nutritional status.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some study refuting the association between anemia & fatigue [17][18][19] and some stating that there is a positive association [10] .…”
Section: Anemia and Cancer Relate Fatigue-is The Association Significmentioning
confidence: 99%
“…305 Poorly controlled pain or inadequately assessed fatigue contribute to psychological distress and impairment of physical and social functioning. 158,[306][307][308][309] Patients with metastatic disease have a significantly greater unmet need for assistance with physical aspects of daily living compared with the needs of patients in remission. 310 …”
Section: Physical Issues Towards the End Of Lifementioning
confidence: 99%